Production of Keratinase by Bacillus sp. FK 28 Isolated in Thailand - Pissuwan, Dakrong; Suntornsuk, Worapot (Agriculture and Natural Resources, 2001)
Screening for keratinase-producing bacteria and their keratinase production were investigated. Fifty two keratinase-producing bacterial strains were isolated from soils in Thailand on a semi-solid agar medium containing 5% feather powder as a substrate at 37°C. They produced keratinase in a range of 0.7-2.6 U/ml by shaking cultivation. The best keratinase producer was designated as FK 28 closely related to Bacillus. Keratinase was produced maximally in the medium containing 1% feather meal with an initial pH of 7.5 under cultivation conditions at 37°C and 150 rpm shaken.